PERAN WORLD FOOD PROGRAMME (WFP) DALAM MEMBANTU MENINGKATKAN KETAHANAN PANGAN DI INDONESIA TAHUN 2012-2015 - Khesia Khorinna, Made Ayu; Fasisaka, Idin; Suwecawangsa, Adi P. (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 2 (2018), 2018)
ABSTRACT Fulfillment of the food security in Indonesia has been pursued since the pre-reform era. One significant cause in meeting the desired level of food security in Indonesia is the population’s over-growth. WFP is an organization that was originally formed as a program that distributes food to disaster areas, but with increasingly dynamic and broad problems, WFP is also recognized by the United Nations and moves under the auspices of the General Assembly. The problems faced are also increasingly widespread in the field of food fulfillment.Since 2012, WFP changed its role in Indonesia from organizations that provide direct assistance to become a strategic partner for Indonesia. Where they act more as consultants who help Indonesia in finding sources of food problems. WFP itself is more concentrated in analyzing and assisting Indonesia in policies related to food security.   Keywords : food security, Indonesia, WFP, international organization